2019
DOI: 10.1111/jce.14127
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation of premature ventricular complexes with low intraprocedural burden guided exclusively by pace‐mapping

Abstract: Background Catheter ablation (CA) of idiopathic premature ventricular complexes (PVCs) is typically guided by both activation and pace‐mapping, with ablation ideally delivered at the site of the earliest local activation. However, activation mapping requires sufficient intraprocedural quantity of PVCs. This study aimed to investigate the outcome of CA of infrequent PVCs guided exclusively by pace‐mapping. Methods We retrospectively analyzed all patients undergoing CA of idiopathic PVCs between 2014 and 2017. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…This is not surprising, as more challenging ablation of deep septal, papillary or epicardial PVCs would be expected to require more RF and fluoroscopy time, as has been shown previously. 2,3,8 In our study, RV compared with LV sites were also more likely to be associated with long term success, consistent with previous studies. Latchemsetty et al 3 reported that highest long-term success rates were achieved with RVOT ablation (82%), and lowest with LV papillary muscle ablation (60%).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This is not surprising, as more challenging ablation of deep septal, papillary or epicardial PVCs would be expected to require more RF and fluoroscopy time, as has been shown previously. 2,3,8 In our study, RV compared with LV sites were also more likely to be associated with long term success, consistent with previous studies. Latchemsetty et al 3 reported that highest long-term success rates were achieved with RVOT ablation (82%), and lowest with LV papillary muscle ablation (60%).…”
supporting
confidence: 92%
“…Radiofrequency catheter ablation (RFCA) is an effective treatment for symptomatic, idiopathic premature ventricular complexes (PVCs) and can improve cardiac function in patients with PVC mediated cardiomyopathy. 1,2 Activation mapping is the preferred strategy to localize the site of origin and guide successful ablation. Short-term outcomes in patients undergoing RFCA in the contemporary era are excellent with a large multicenter retrospective cohort study demonstrating an overall acute success rate of 84% (range, 67%-93%).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using primarily pace mapping to guide ablation of idiopathic VA Shirai and colleagues 5 recently described a similar PM approach in 24 patients with low intraprocedural burden of PVCs originating from any ventricular site. Patients included were similar in demographics to our study, the majority with a diagnosis of idiopathic PVCs and 2 patients with impaired LV ejection fraction ,50%, secondary to PVC-induced cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Although results are encouraging, these studies are limited by a small number of patients, with reported freedom from clinical VA between 79% and 100%, during medium-term follow-up. 4,5 In this study we sought to compare outcomes among patients with low intraprocedural burden of idiopathic outflow tract VA who received ablation guided by a PM approach vs patients with frequent intraprocedural idiopathic outflow tract VA undergoing standard activation-guided ablation (non-PM). We hypothesized that the 2 techniques would have comparable outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Second, in patients with infrequent PVCs at the beginning of the procedure, infusion of isoproterenol or low‐dose adrenalin can often induce a sufficient number of PVCs for reliable activation mapping and ablation 17 . Third, pace‐mapping during sinus rhythm in addition to activation mapping, can be particularly useful in ablation procedures with infrequent PVCs 18 . However, pace mapping might be adequate for PVCs in some locations (RVOT), but not in others (e.g., aortic cusps, within the LV superior septum, etc.).…”
Section: Discussionmentioning
confidence: 99%